Elucidation of ionic interactions in the protic ionic liquid solutions by isothermal titration calorimetry - Rai, Gitanjali; Kumar, Anil (Journal of Physical Chemistry B, 2014)
The strong hydrogen-bonded network noted in protic ionic liquids (PILs) may lead to stronger interactions of the ionic entities of PILs with solvents (water, methanol, ethylene glycol, climethylsulfoxide (DMSO), N,N'-dimethylformamide (DMF)) as compared with those of aprotic ionic liquids (APILs). The PILs used in this work are 1-methylimidazolium tetrafluoroborate, 2-methylpyridinium tetrafluoroborate, and N-methylpyrrolodinium tetrafluoroborate in comparison to 1-butyl-3-methylimidazolium tetrafluoroborate, which is classified as an APIL. In this work, the excess partial molar enthalpy, H-IL(E) obtained from isothermal calorimetric titrations at 298.15 K is used to probe the nature of interactions of the PIL cations with solvent molecules against those present in APIL solvent systems. This work also reports interesting flip-flopping in the thermal behavior of these PIL-solvent systems depending upon the structure of the cationic ring of a PIL. In some cases, these flip-flops are the specific fingerprints for specific PILs in a common solvent environment. The excess partial molar enthalpy at infinite dilution, H-IL(E,infinity), of these PILs bears a critical dependence on the solvent properties. An analysis of relative apparent molar enthalpies, phi(L), of the PIL solutions by the ion interaction model of Pitzer yields important information on ionic interactions of these systems.